PRELIMINARY PHYTOCHEMICAL INVESTIGATIONS ON THE ANTIRHEUMATIC PRINCIPLES IN ANISOLMELES MALABARICA R.BR., AND CLERODENDRUM SERRATUM L.: Pharmaceutical Science-Pharmacognosy & Phytochemistry - SHAREEF.M, ISMAIL; S., LEELAVATHI.; MOHAN REDDY, JAGAN; M., ABHILASH. (International Journal of Life Science and Pharma Research, 2011)
Phytochemical investigations were undertaken on the Antirheumatic principles of Anisolmeles malabarica R.Br., (Lamiaceae) and Clerodendrum serratum L. (Verbenaceae). Phytochemical analysis of the aerial parts of the plant extracts showed that both these plants have major Antirheumatic principles belonging to alkaloids, flavanoids and glycosides group. These compounds have been subjected to analysis using TLC techniques. Conformation of the chemical structure using modern analytical techniques is suggested to isolate and characterize the exact chemical compounds that may help in treating rheumatic complaints.